Kehidupan beragama masyarakat Kadazandusun - Suraya Sintang (Kota Kinabalu, Sabah : Penerbit Universiti Malaysia Sabah, 2007)
Religion and religious life of the Kadazandusun people in Ranau, Sabah.
Revision of the author's thesis (master's)--Universiti Kebangsaan Malaysia.
Includes bibliographical references (p. [175]-178) and index.
In Malay
Keywords: Dusun (Bornean people) -- Religion; Ranau (Sabah) -- Religious life and customs